Virulence patterns of Staphylococcus aureus strains from nasopharyngeal colonization - Deinhardt-Emmer, S.; Sachse, S.; Geraci, J.; Fischer, C.; Kwetkat, A.; Dawczynski, K.; Tuchscherr, L.; Löffler, B. (The Journal of hospital infection, 2018)
The prevalence of nasopharyngeal colonization with Staphylococcus aureus can reach 20–30% among the population, which can lead to invasive infection. To investigate the prevalence of colonization among different age groups, and analyse S. aureus strain-specific virulence patterns. For analysis of the prevalence of colonization, groups consisting of newborns, healthy volunteers aged 5–60 years, and nursing home residents aged >80 years were examined with nasopharyngeal swabs. After S. aureus was cultured, genetic analysis and phenotypic virulence testing were performed by cell-based assays. Among 924 volunteers, the overall colonization rate was approximately 30%, with a peak in subjects aged 5–10 years (49%). Neonates and subjects aged >80 years showed different distributions of clonal clusters. Overall, the strains of all age groups exhibited virulence characteristics that can contribute to the development of infection. In particular, the neonatal strains exhibited a high incidence of toxin genes that resulted in increased cytotoxic effects compared with the other strains tested. Colonizing strains showed a virulence profile in all age groups, which may lead to the establishment of invasive infection. Consequently, decolonization measures could be considered for selected patients depending on the risk of infection.